Penggunaan Teknologi Informasi Dan Komunikasi (TIK) Dalam Pelayanan Publik - Hidayat, Dayat (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2009)
It is a government compulsary to enhance better services for their citizens. Many rules and efforts are created to make these services more convenient. The use of a informations and technology is one of the efforts to make the services closser to the citizens, it called e-government.